The Effect of Think Talk and Write Learning Model Assisted by Video Learning Media on Social Studies Learning Interest of Elementary School Students - Suparti , Dian; Suardi, Suardi; Idawati, Idawati (Journal of Educational Sciences, 2025)
Student motivation is crucial for effective learning, especially in Social Studies (IPS), where understanding complex social concepts is key. This study examines the impact of the Think Talk and Write (TTW) learning model supported by video media on the learning interest of fourth-grade students at Elementary School D Cluster 2, Bontomarannu District, Gowa Regency. Using a quasi-experimental design, the experimental group received TTW with video assistance, while the control group followed conventional teaching. Learning interest was measured through a validated questionnaire before and after the intervention. Results showed a significant increase in the experimental group’s interest, rising from moderate to high, whereas the control group’s improvement was marginal. The TTW model combined with video media enhanced cognitive and affective engagement by encouraging reflection, discussion, and writing, supported by interactive multimedia. This approach also minimized variability in student motivation, promoting consistent engagement. The findings support the effectiveness of cooperative learning augmented by multimedia in enhancing motivation in primary Social Studies, especially where innovative methods are limited. This study provides empirical evidence encouraging educators to adopt multimodal, learner-centered strategies. Further research should investigate long-term impacts and qualitative student experiences.